ПЛАНИРОВАНИЕ РАССЛЕДОВАНИЯ ПРЕСТУПЛЕНИЙ, СОВЕРШАЕМЫХ ПУТЕМ МОШЕННИЧЕСТВА С ФИНАНСОВЫМИ РЕСУРСАМИ (Journal of actual problems of jurisprudence, 2019)
The paper deals with planning the investigation of crimes committed by fraud with credit and financial resources to organize thework of the investigator.